2009
DOI: 10.1002/poc.1592
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substituent groups of porphyrins on the electroluminescent properties of porphyrin‐doped OLED devices

Abstract: Six tetraphenylporphyrins (TRPPH2) with different horizontal substituents R (R = H, CH3, OH, F, Cl, Br) were synthesized, and the organic light‐emitting diode (OLED) devices with a general configuration of ITO/TPD/Alq3:2%TRPPH2/Alq3/Al were prepared. The substituted TRPPH2 was used as the host dopant, 4,4‐bis‐(m‐tolyphenylamino)biphenyl (TPD) was used as a hole‐transporting material, and aluminum tris(8‐quinolinolato) (Alq3) was used as an electron‐transporting material. The electroluminescent (EL) properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Several studies use porphyrin as a dopant, in which they increased the number of layers, and the device performance depended on the effective overlap of energy transfer from the electron carrier (host) to the dopant (guest). Therefore, it is important to highlight that in this study, the porphyrins were not used as dopants, and that they showed an electroluminescence in the red and a threshold voltage, which is similar to that reported in other works involving porphyrins as an emitter layer [8,9,14,15,46,47].…”
Section: Resultssupporting
confidence: 81%
“…Several studies use porphyrin as a dopant, in which they increased the number of layers, and the device performance depended on the effective overlap of energy transfer from the electron carrier (host) to the dopant (guest). Therefore, it is important to highlight that in this study, the porphyrins were not used as dopants, and that they showed an electroluminescence in the red and a threshold voltage, which is similar to that reported in other works involving porphyrins as an emitter layer [8,9,14,15,46,47].…”
Section: Resultssupporting
confidence: 81%
“…Furthermore, different chemical functionalities can be incorporated into the periphery of the macrocycle serving, for instance, as anchoring groups on different substrates. Porphyrin molecules attached to solid surfaces are therefore relevant for molecular devices including gas sensors, organic light‐emitting devices, catalysts and photovoltaic cells . In many of these systems, the porphyrin molecules are attached to oxide substrates, which makes fundamental studies on the adsorption and interaction of porphyrin molecules with oxide surfaces important.…”
Section: Introductionmentioning
confidence: 99%
“…1 Because of their unique optical properties, porphyrins can be employed as sensitizers for photovoltaic 2 nanoscale devices, sensors 3 or as components of organic light emitting diodes. 4 Furthermore, porphyrins possess easily accessible and stable cationic and anionic states that can be exploited in the construction of molecular wires, 5 transistors 6 and molecular memories. 7 The introduction of redox-active substituents such as ferrocene in the meso or b-pyrrolic position results in additional redox processes thus extending their applicative potentiality.…”
mentioning
confidence: 99%